2010
DOI: 10.1080/09654311003701480
|View full text |Cite
|
Sign up to set email alerts
|

Space and Social Capital: The Degree of Locality in Entrepreneurs' Contacts and its Consequences for Firm Success

Abstract: Social capital is valuable for entrepreneurs starting a business. Although many small businesses are located at the entrepreneurs' dwelling, little is known about entrepreneurs' local ties and their relevance for firm success. Distinguishing between local and non-local social capital, this contribution looks at the following: (1) The availability of local social capital (2) The relation between social capital and local social capital, and characteristics of firms and entrepreneurs (3) The relation between soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…This is a break with an older tradition that focused on the individual attributes and psychological profiles of entrepreneurs (Dodd and Anderson, 2007). Entrepreneurs draw the resources they require to start and grow the firm through their personal and professional social networks, with the densest and strongest connections often found within their local environment (Schutjens and Völker, 2010). The quality of the social capital and networks of a community will therefore have a significant impact on the ability of entrepreneurs to gather the information, resources, and support they require.…”
Section: Entrepreneurial Environments and Contextsmentioning
confidence: 99%
“…This is a break with an older tradition that focused on the individual attributes and psychological profiles of entrepreneurs (Dodd and Anderson, 2007). Entrepreneurs draw the resources they require to start and grow the firm through their personal and professional social networks, with the densest and strongest connections often found within their local environment (Schutjens and Völker, 2010). The quality of the social capital and networks of a community will therefore have a significant impact on the ability of entrepreneurs to gather the information, resources, and support they require.…”
Section: Entrepreneurial Environments and Contextsmentioning
confidence: 99%
“…However, the weakness of these studies is that they often confine their analysis to local interactions, leaving aside extra-regional linkages. As local social networks are larger and interaction more regular in urban regions [28,33,34], social capital is considered lower in rural areas, which again may leave them with a disadvantage regarding entrepreneurial dynamics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first set of studies takes a relational perspective and emphasizes that the social capital of entrepreneurs is important for their success [32][33][34]. As Westlund and Bolton [35] argue, the primary role of social capital is to give small firms a producer surplus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By doing this, firms have the chance to communicate with each other, and they establish internal mutual trust. Schutjens and Völker's (2010) study of 385 Germany enterprises found that the enterprises' economic performance is tightly tied to the local network.…”
Section: Relations Among Regionally Homogenous Clusters In the Same Rmentioning
confidence: 99%